Physical violence by men and psychosis in a mental health setting: associations with symptom profile, treatment engagement, and psychosocial stressors. Issue 5 (2nd September 2020) - Joubert, David; Zaumseil, Blake
ABSTRACT: Physical violence is a significant problem in forensic mental health institutions, being associated with a variety of negative outcomes for both inpatients and staff. In this study, associations between mental health symptom profile, treatment engagement, the experience of stressors and trajectories of physical aggression were examined in a sample of 3293 men institutionalized in a forensic mental health setting with an initial diagnosis of psychotic disorder. Data were collected for up to seven time points, equivalent to a roughly 18-month follow-up period. Three distinct trajectories of aggression were identified. The vast majority (approx. 90%) of inmates did not show a significant or consistent pattern of aggressive behavior. A small subgroup (approx. 1 in 43 individuals) presented with a pattern of increasing aggressive acting-out. Another group (approx. 1 in 15 individuals) exhibited a somewhat higher probability of aggression at baseline, with a moderate progressive decline over time. These groups were differentiated on the basis of symptom profile, level of insight and specific psychosocial stressors. Findings suggest that institutional aggression in men with psychosis appears to be multi-determined, with active symptoms, deficits in self-awareness and the experience of stressors all playing a role in accounting for its presence and evolution over time.